Impact of Exclusion on Minoritized Learners: Promoting Educational Equity as an Imperative for Sustainable Development - Nwachukwu, Emmanuel Lucas; Chukwuma, Victoria Azuka; Ubani, Gift Adaoma; Nwokorie, Godson Chidi; Joseph, Christopher Chinedu (Journal of Education Method and Learning Strategy, 2025)
Despite global advocacy for educational equity, many educational systems across the world continue to fail in providing a truly inclusive education especially directed to disadvantaged learners like those from low-income families, and those from ethnic and racial minorities who may encounter systemic bias, thus exacerbating cycles of social inequity. This raises critical concern about the systemic barriers faced by minoritized learners such as persistent issue of underrepresentation, economic disparities, discrimination and bias, and unequal access to resources, and the broader implications of these barriers on social development, which consequently limits their potential for personal and social advancement. This review paper examines how inclusive education rooted in equity-focused policies and practices can empower marginalized learners by enhancing their academic and career opportunities, thereby advancing social mobility, this, in turn, ensures broader social development by reducing inequalities and promoting inclusive growth. The method adopted to examine this topic is literature-based analyses, which will help to build a comprehensive understanding of the issues raised, identify effective strategies, and recognize areas needing improvement for further study. The paper concludes that there is need for widespread policy changes and a concerted effort by educators, policymakers, and other critical stakeholders to prioritize inclusivity in education, to create equitable, socially responsible education systems that leave no learner behind, reduce inequalities and broaden social development which represents the broad improvements in societal well-being and progress that arise when all individuals have equitable opportunities to succeed.